The Bank, the States, and the Market: An Austro-Hungarian Tale for Euroland, 1867-1914 - Marc Flandreau (Oesterreichische Nationalbank (OeNB), 2001)
In 1867, the "Compromise" between Austria and Hungary laid the foundation of a single currency system with a common central bank. As in today's euroland, each part of the monarchy remained sovereign in fiscal matters. Moreover, the borrowing needs of both parts of the monarchy were quite large, since Austria and Hungary sought to promote their own economic development through government spending. Yet no 'fiscal stability pact' existed: the two countries could run deficits to the extent of the public's willingness to lend to them. They were thus only subjected to the discipline of the capital market. This paper documents the record of the Austro-Hungarian monetary union and shows how this discipline led to a process of increased power of the central bank.
Keywords: D92; E22; C23; G31; G32; 330; Credit channel; balance sheet channel; investment; panel data